Olah Data Matematika dan Statistik Sebagai Penunjang Kewirausahaan - Etika Sabariah (Juripol (Jurnal Institusi Politeknik Ganesha Medan), 2020)
Like to known , businessman increase growth up always every time. Because high cost living, depreciation value money, there are opportunity, high competitor at world working make the people choice become businessman. Like to known think obout strategic is must to do. On business, activity always influence by environmental until need manajemen and technology application and rich knowledgement economic science, manajemen strategic and another supporter factor. So to support strategic business, businessman need training about data manner with using mathematic and statistic to help make decisition. So actor from academic very help them, with training that is giving as shape tri duty